2023
DOI: 10.1002/inmd.20220012
|View full text |Cite
|
Sign up to set email alerts
|

Cell membrane biomimetic nanomedicines for cancer phototherapy

Abstract: Phototherapy, mainly including photothermal therapy (PTT) and photodynamic therapy (PDT), can kill cancer cells by generating heat or reactive oxygen species, which has the advantages of being minimally invasive, high efficiency, and low toxicity. However, traditional phototherapeutic agents face challenges such as poor tumor targeting, susceptibility to passive immune clearance, and suboptimal biocompatibility, which limit their clinical application. Recently, cell membrane biomimetic technology endows photot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 175 publications
1
18
0
Order By: Relevance
“…As a key participator, inflammatory response usually occurs after injury and influences various pathogenic processes, such as cancer, IVDD, and IVDD-evoked pain, by inducing abundant releases of proinflammatory mediators and cytokines. ,, A growing body of evidence supports the fact that IVDD is commonly accompanied by increased levels of proinflammatory cytokines, such as IL-1β. , Notably, abundant production of these inflammatory factors will induce a local inflammatory response, which facilitates the catabolism of ECM and leads to the dysfunction and structural changes of IVD. , For instance, inflammatory mediator iNOS plays an important role in the inflammatory processes via accelerating the production of NO, thereby triggering the progression of IVDD . In this study, IL-1β exposure enhanced the expression levels of inflammatory mediator iNOS, NO, and inflammatory cytokine IL-6 and TNF-α in human NPCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a key participator, inflammatory response usually occurs after injury and influences various pathogenic processes, such as cancer, IVDD, and IVDD-evoked pain, by inducing abundant releases of proinflammatory mediators and cytokines. ,, A growing body of evidence supports the fact that IVDD is commonly accompanied by increased levels of proinflammatory cytokines, such as IL-1β. , Notably, abundant production of these inflammatory factors will induce a local inflammatory response, which facilitates the catabolism of ECM and leads to the dysfunction and structural changes of IVD. , For instance, inflammatory mediator iNOS plays an important role in the inflammatory processes via accelerating the production of NO, thereby triggering the progression of IVDD . In this study, IL-1β exposure enhanced the expression levels of inflammatory mediator iNOS, NO, and inflammatory cytokine IL-6 and TNF-α in human NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…20 As a key participator, inflammatory response usually occurs after injury and influences various pathogenic processes, such as cancer, IVDD, and IVDD-evoked pain, by inducing abundant releases of proinflammatory mediators and cytokines. 5,9,35 A growing body of evidence supports the fact that IVDD is commonly accompanied by increased levels of proinflammatory cytokines, such as IL-1β. 7,36 Notably, abundant production of these inflammatory factors will induce a local inflammatory response, which facilitates the catabolism of ECM and leads to the dysfunction and structural changes of IVD.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The original text has been updated and accurately reflects these advancements [16,17]. This biomimetic design strategy and the associated functionality of nanoparticles provide a new horizon for drug delivery and disease treatment [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the enzymes could be preloaded in nanomaterials with porous structure, followed by coating a lipid membrane to improve the pharmacokinetics and stability. However, in this approach, the release of the embedded enzymes is hard to control, and the poor biodegradability and the long-term toxicity of most nanomaterials compromised their practical applications . Evidence shows that the lipid membrane-based nanovesicles themselves perform superior properties than most nanomaterials in biocompatibility, immunogenicity, and clinical transformation potential () as drug delivery systems . Thus, loading enzymes directly into lipid membrane-based nanovesicles should be a promising strategy.…”
mentioning
confidence: 99%